Opposing effects of Toll-like receptors 2 and 4 on synaptic stability in the spinal cord after peripheral nerve injury - Freria, Camila Marques (BioMed Central, 2012)
BACKGROUND: Glial cells are involved in the synaptic elimination process that follows neuronal lesions, and are also responsible for mediating the interaction between the nervous and immune systems. Neurons and glial cells express Toll-like receptors (TLRs), which may affect the plasticity of the central nervous system (CNS). Because TLRs might also have non-immune functions in spinal-cord injury (SCI), we aimed to investigate the influence of TLR2 and TLR4 on synaptic plasticity and glial reactivity after peripheral nerve axotomy. METHODS: The lumbar spinal cords of C3H/HePas wild-type (WT) mice, C3H/HeJ TLR4-mutant mice, C57BL/6J WT mice, and C57BL/6J TLR2 knockout (KO) mice were studied after unilateral sciatic nerve transection. The mice were killed via intracardiac perfusion, and the spinal cord was processed for immunohistochemistry, transmission electron microscopy (TEM), western blotting, cell culture, and reverse transcriptase PCR. Primary cultures of astrocytes from newborn mice were established to study the astrocyte response in the absence of TLR2 and the deficiency of TLR4 expression. RESULTS: The results showed that TLR4 and TLR2 expression in the CNS may have opposite effects on the stability of presynaptic terminals in the spinal cord. First, TLR4 contributed to synaptic preservation of terminals in apposition to lesioned motor neurons after peripheral injury, regardless of major histocompatibility complex class I (MHC I) expression. In addition, in the presence of TLR4, there was upregulation of glial cell-derived neurotrophic factor and downregulation of interleukin-6, but no morphological differences in glial reactivity were seen. By contrast, TLR2 expression led to greater synaptic loss, correlating with increased astrogliosis and upregulation of pro-inflammatory interleukins. Moreover, the absence of TLR2 resulted in the upregulation of neurotrophic factors and MHC I expression. CONCLUSION: TLR4 and TLR2 in the CNS may have opposite effects on the stability of presynaptic terminals in the spinal cord and in astroglial reactions, indicating possible roles for these proteins in neuronal and glial responses to injury.